2018
DOI: 10.1186/s12870-018-1285-6
|View full text |Cite
|
Sign up to set email alerts
|

The parthenocarpic gene Pat-k is generated by a natural mutation of SlAGL6 affecting fruit development in tomato (Solanum lycopersicum L.)

Abstract: BackgroundParthenocarpy is a desired trait in tomato because it can overcome problems with fruit setting under unfavorable environmental conditions. A parthenocarpic tomato cultivar, ‘MPK-1’, with a parthenocarpic gene, Pat-k, exhibits stable parthenocarpy that produces few seeds. Because ‘MPK-1’ produces few seeds, seedlings are propagated inefficiently via cuttings. It was reported that Pat-k is located on chromosome 1. However, the gene had not been isolated and the relationship between the parthenocarpy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 44 publications
(42 reference statements)
3
35
0
Order By: Relevance
“…This result suggested that pat-2 was involved in regulating fruit weight. However, it was reported that in an F 2 population from 'Micro-Tom' and 'MPK-1', a quantitative trait locus (QTL) for pollinated fruit weight was detected on chromosome 4, where pat-2 is positioned (Takisawa et al, 2018). Although both 'Micro-Tom' and 'MPK-1' alleles at the pat-2 locus are homozygous for the Pat-2 allele, the QTL was detected.…”
Section: Resultsmentioning
confidence: 99%
“…This result suggested that pat-2 was involved in regulating fruit weight. However, it was reported that in an F 2 population from 'Micro-Tom' and 'MPK-1', a quantitative trait locus (QTL) for pollinated fruit weight was detected on chromosome 4, where pat-2 is positioned (Takisawa et al, 2018). Although both 'Micro-Tom' and 'MPK-1' alleles at the pat-2 locus are homozygous for the Pat-2 allele, the QTL was detected.…”
Section: Resultsmentioning
confidence: 99%
“…After screening parthenocarpic F 2 plants, which were considered to be homozygous for the pat-k allele by examining the expansion of unpollinated ovaries, the selected plants were backcrossed with 'Micro-Tom' as the recurrent parent. After the process was repeated four times, the resulting BC 5 plants were selfed to obtain BC 5 F 2 plants homozygous for the pat-k allele, which were selected using two DNA markers, an insertion/ deletion marker, Del22-1 (SL2.50: 85354768-85355860), and a cleaved amplified polymorphic sequence marker, SNP19 (Takisawa et al, 2018), flanking the pat-k locus (Table S1).…”
Section: Plant Materials and Plant Growth Conditionsmentioning
confidence: 99%
“…Total RNA was extracted using Sepasol ® -RNA I Super G (NACALAI TESQUE, INC., Kyoto, Japan), according to the manufacturer's instructions, and was used for cDNA synthesis using a ReverTra Ace qPCR RT Kit (TOYOBO CO., LTD., Osaka, Japan). Quantitative RT-PCR was performed as described previously (Takisawa et al, 2018). Table S2 lists primers used for quantitative RT-PCR.…”
Section: Quantitative Rt-pcr Analysis Of Slagl6mentioning
confidence: 99%
See 1 more Smart Citation
“…The parthenocarpic genotypes Soressi and Montfavet191 are controlled by a single recessive pat, while Severianin is controlled by a single recessive pat-2 and MPK-1 is controlled by a single recessive Pat-k. The RP75/59, IL5-1, and IVT-line1 tomatoes are controlled by the recessive genes pat3/pat4, pat4.1/pat5.1, and pat4.2/pat9.1, respectively (Takisawa et al 2018).…”
Section: Introductionmentioning
confidence: 99%